Imaging of kiss-and-run exocytosis of surface receptors in neuronal cultures - Roman-Vendrell, Cristina; Chevalier, Michael; Acevedo-Canabal, Agnes M.; Delgado-Peraza, Francheska; Flores-Otero, Jacqueline; Yudowski, Guillermo A. (Frontiers in Cellular Neuroscience, 2014)
Transmembrane proteins are continuously shuttled from the endosomal compartment to the neuronal plasma membrane by highly regulated and complex trafficking steps. These events are involved in many homeostatic and physiological processes such as neuronal growth, signaling, learning and memory among others. We have previously shown that endosomal exocytosis of the B2 adrenergic receptor (B2AR) and the GluR1-containing AMPA receptor to the neuronal plasma membrane is mediated by two different types of vesicular fusion. Transient events in which receptors are delivered to the plasma membrane in a single kinetic step, and persistent events in which receptors remain clustered at the insertion site for a variable period of time before delivery to the cell surface. Here, by comparing the exocytosis of multiple receptors in dissociated hippocampal and striatal cultures, we show that persistent events are a general mechanism of vesicular delivery. Persistent events were only observed after 10 days in vitro, and their frequency increased with use of the calcium ionophore A23187 and with depolarization induced by KCl. Finally, we determined that vesicles producing persistent events remain at the plasma membrane, closing and reopening their fusion pore for a consecutive release of cargo in a mechanism reminiscent of synaptic kiss-and-run. These results indicate that the delivery of transmembrane receptors to the cell surface can be dynamically regulated by kiss-and-run exocytosis.